A critique of the ideas of ethics and morals in light of the eighth SDG - Jaspe Nieto, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The essay exposes the ideas of Ethics and Morality in their connection with the achievement of goals 8.5 and 8.8 of the Sustainable Development Goal 8 of the 2030 Agenda. Throughout this analysis, the author develops an explanation of the possible conflicts generated because of problems of an ethical and moral nature in the application of business policies oriented towards economic sustainability. To do this, firstly defines the notions, later confront them, and, finally, conclude solutions as a synthesis of a dialectical process. In parallel, these terms are presented in their correspondence with the idea of sustainability from a socioeconomic and political context that starts from the ideological system of the culture that generates it.
Keywords: ethics; morals; sustainability; company policy